Growth and physicochemical characterization of cherry tomato under irrigation with saline water and nitrogen fertilization - Almeida Roque, Iara; Almeida dos Anjos Soares , Lauriane; Soares de Lima , Geovani; Pereira Lopes, Iracy Amelia; Chaves de Almeida, Alan Keis; Gomes de Oliveira, Sabrina (Comunicata Scientiae, 2022)
Saline water is an alternative to the low availability of high-quality water in semi-arid regions. However, although these water sources negatively affect most crops, their use allied to management practices aiming to mitigate the effects of salts has been increasingly studied, including nitrogen fertilization. From this perspective, this study aimed to evaluate the growth and physicochemical characterization of cherry tomato plants irrigated with saline water and nitrogen fertilization. The experiment was conducted under field conditions at the Center of Sciences and Agrifood Technology of the Federal University of Campina Grande in Pombal – PB, using a randomized block design arranged as a 5 × 5 factorial referring to five electrical conductivity levels of irrigation water - ECw (0.3, 1.3, 2.3, 3.3, and 4.3 dS m-1) and five nitrogen doses - ND (50, 75, 100, 125, and 150% of the N recommendation), with three replications. The nitrogen doses did not mitigate the effects of salt stress on plant height and stem diameter of cherry tomato. However, irrigation with the electrical conductivity of 3.3 dS m-1 increased the soluble solids of cherry tomato fruits.